2015
DOI: 10.1038/nature14625
|View full text |Cite
|
Sign up to set email alerts
|

The ancestry and affiliations of Kennewick Man

Abstract: Kennewick Man, referred to as the Ancient One by Native Americans, is a male human skeleton discovered in Washington state (USA) in 1996 and initially radiocarbon-dated to 8340–9200 calibrated years BP1. His population affinities have been the subject of scientific debate and legal controversy. Based on initial study of cranial morphology it was asserted that Kennewick Man was neither Native American nor closely related to the Claimant Plateau tribes of the Pacific Northwest, who claimed ancestral relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(172 citation statements)
references
References 25 publications
5
161
2
4
Order By: Relevance
“…Under this scenario, the split between the Ainu and Native American ancestors is likely to have occurred earlier than the gene flow of western Eurasian ancestry into the Native American ancestors (Raghavan et al 2014), because the Ainu and other East Asians are symmetrically related to contemporary Europeans and to the ancient MA1 sample (Table S2). However, a recent study reported no genetic affinity between the Ainu and the Kennewick man (Rasmussen et al 2015). An alternative to this scenario is that there may have been more recent gene flow between the Ainu and northeast Siberian populations ("scenario 2" in Figure 5B).…”
Section: Discussionmentioning
confidence: 98%
“…Under this scenario, the split between the Ainu and Native American ancestors is likely to have occurred earlier than the gene flow of western Eurasian ancestry into the Native American ancestors (Raghavan et al 2014), because the Ainu and other East Asians are symmetrically related to contemporary Europeans and to the ancient MA1 sample (Table S2). However, a recent study reported no genetic affinity between the Ainu and the Kennewick man (Rasmussen et al 2015). An alternative to this scenario is that there may have been more recent gene flow between the Ainu and northeast Siberian populations ("scenario 2" in Figure 5B).…”
Section: Discussionmentioning
confidence: 98%
“…(14). Kennewick Man also displays surprising results as an early Holocene individual who resided in the Pacific Northwest.…”
Section: Significancementioning
confidence: 96%
“…Haplogroups observed in Checua remains, listed from highest to lowest frequency, were: A2 (N = 7), B2 (N = 3), C1 (N = 1) and D4h3a (N = 1) (see Table 2). The X2a haplogroup was not detected in Checua samples, which is not surprising since X2a is restricted to northern North America and Europe (Perego, et al 2009, Rasmussen, et al 2015. The observed haplogroups can be distinguished according to human occupation zones [I = Stratum 4, and II = Stratum 5 (Tables 1, 2)].…”
Section: Identification Of Mtdna Haplogroups and Haplotypesmentioning
confidence: 90%